Biomechanical evaluation of a novel minimally invasive pedicle bone cement screw applied to the treatment of Kümmel’s disease in porcine vertebrae - Ma, Xiang; Feng, Qing; Zhang, Xingze; Sun, Xiaolei; Lin, Longwei; Guo, Lin; An, Lijun; Cao, Shenglin; Miao, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Background and objective: Treatment of Kümmel's Disease (KD) with pure percutaneous kyphoplasty carries a greater likelihood of bone cement displacement due to hardened bone and defect of the peripheral cortex. In this study, we designed a novel minimally invasive pedicle bone cement screw and evaluate the effectiveness and safety of this modified surgical instruments in porcine vertebrae.Methods: 18 mature porcine spine specimens were obtained and soaked in 10% formaldehyde solution for 24 hours. 0.5000 mmol/L EDTA-Na 2 solution was used to develop in vitro osteoporosis models of porcine vertebrae. They were all made with the bone deficiency at the anterior edge of L1. These specimens were randomly divided into 3 groups for different ways of treatment: Group A: pure percutaneous kyphoplasty (PKP) group; Group B: unilateral novel minimally invasive pedicle bone cement screw fixation combined with PKP group; Group C: bilateral novel minimally invasive pedicle bone cement screw fixation combined with PKP group. The MTS multi-degree of freedom simulation test system was used for biomechanical tests, including axial loading of 500 N pressure, range of motion (ROM) in flexion, extension, left /right lateral bending, and left/right axial rotation at 5 Nm, and the displacement of bone cement mass at maximum angles of 5° and 10°.The three groups were well filled with bone cement, no leakage or displacement of bone cement was observed, and the height of the vertebrae was higher than preoperation (P<0.05). In the left /right axial rotation, the specimens were still significantly different (P<0.05) from the intact specimens in terms of ROM after PKP. In other directions, ROM of all group had no significant difference(P<0.05) and was close to the intact vertebrae. Compared with PKP group, the relative displacement of bone cement in groups B and C was smaller (P<0.05).In the in vitro animal vertebral models, the treatment of KD with the placement of novel pedicle minimally invasive bone cement screw combined with PKP can effectively restore the vertebral height, improve the stability of the affected vertebra and prevent the displacement of bone cement. Biomechanically, there is no significant difference between bilateral and unilateral fixation.